Automatic cleaning system of sample preparation of flue gas tester - Корнієнко, Дмитро Григорович; Приміський, Владислав Пилипович (Technology audit and production reserves, 2015)
It is shown a detailed description of the operation of the automatic cleaning at different modes and levels of concentration of dust and gas stream pollution of flue gas. The basis of an automatic cleaning system of dust filters before gas analyzers based on the principle of a closed system of automatic control. The system constantly compares the real current flow rate with a fixed current pre-entered in the control unit. The control unit sends a signal to the switching system of solenoid valves when reducing the flow of the sample, due to contamination (clogging) of filters below a fixed level and with the help of flow booster begins to reverse blowing of dust filter from dust in the chimney. During investigation it is found that the best operation mode of system actuation is a 25-30 % decrease in the expense of the nominal value of the primary sample flow while "clean" filter. Another important feature of the system is the choice of performance and power of flow boosters for blowdown. The power of flow booster was 1,5-2,0 kW during investigations on the smokestacks of coal boilers, TPC with the dust concentration of 120-150 mg/m3 with ensuring a flow rate of smoke samples in the range of 8-10 l/min. The proposed system is simple in construction, does not require a significant investment for its implementation and provides automatic cleaning of dust filters without operator. Automatic cleaning of filter dust is recommended for stationary systems for monitoring the concentration of toxic components of flue gases for industry, energy, cement, brick and asphalt concrete plants, everywhere where the treatment and control of flue gas is carried out by gas analyzers.